Розробка компонентів інформаційної системи тестування для перевірки і оцінювання знань - Шинкарьов, О. С. (ХНУРЕ, 2024)
The report discusses a testing system designed to effectively test and assess students' knowledge of various subject areas. Methods include multiple choice, open-ended questions, and fixed-response tasks. The key components are the database, the test management system and the evaluation system. Application systems allow testing to be automated, shorten its time and ensure high accuracy of results.
Keywords: тестування знань; інформаційна система; оцінювання знань; розробка компонентів; перевірка знань